ANAGRAM-BASED EVALUATION OF GOLEK KUDUP SARI DANCE LEARNING NEEDS FOR JUNIOR HIGH SCHOOL STUDENTS - Nur Rohmayani, Wulan Suci; Lestari, Wahyu (Acintya, 2024)
This research aims to discover the results of the innovation of learning evaluation of Golek Kudup Sari Dance based on anagram games at SMPN 2 Bumijawa.  In general, the dance learning model at SMPN 2 Bumijawa is still conventional including the evaluation process. Furthermore, an online media-based learning and evaluation process was developed. The research method used in this research is Research and Development. The data collected in this research is qualitative data in the form of empirical data. The results showed that anagram game-based evaluation is very efficient to be applied to dance learning at SMPN 2 Bumijawa. The conclusion obtained in the research is that anagram-based Golek Kudup Sari Dance learning is needed by teachers and students as an innovative curriculum implementation. In a sustainable manner, the process of learning dance through online games at SMPN 2 Bumijawa is expected to continue to be applied and developed further.